Vocational education, on-the-job training, and labour market integration of young workers in urban West Africa - (:unkn) unknown (My University, 2014)
Young people in Africa encounter many difficulties in entering the labour market and in searching for decent and productive jobs. Research on the links between formal education and vocational training and their economic returns are especially crucial in understanding the inadequate demand for their labour. This article presents evidence based on the 1-2-3 Surveys conducted in seven West African countries; the surveys provide a consistent and comparable picture of the urban youth employment situation in these countries. The analysis also indicates that vocational education could be helpful in integrating the formal sector and that it often offers better earnings and better firm performance than general education, especially at higher levels of schooling. Overall, young workers with no formal vocational education and training face poorer working conditions, while those who have had a traditional apprenticeship in a small firm occupy an intermediate position. Finally, on-the-job training plays a crucial role in the informal sector of the West African cities.
Keywords: African Research